COVID-19 and team-based healthcare: The essentiality of theory-driven research. Issue 5 (2nd September 2020) - Michalec, Barret; Lamb, Gerri
ABSTRACT: There is evidence to suggest enhanced teamness, heightened interprofessional values and practices, and even the potential for dilution of occupational status hierarchies within healthcare practice and delivery during the time of COVID-19. It is essential that we study these emergent changes using the lens of multilevel theory to better understand these recent developments and their current and future implications for interprofessional practice, education, and policy. Within this article, we first offer a brief overview of secondary data to highlight these COVID-19-specific shifts to provide context and perspective. We then outline prominent micro, meso, and macro-level theories, and propose accompanying rudimentary hypotheses and related general research questions to help guide, and ideally accelerate IPE and IPCP research related to this crisis. Our goal is to not only spotlight key areas for future research during and post COVID-19 but also provide a "starter kit" to encourage more theory-driven research (and theory-expansion) in the IPE and IPCP fields.